Contributions of intramolecular and intermolecular energy changes to strain-induced enthalpy relaxation in uniaxially drawn poly(lactic acid) films. (1st May 2015) - Kim, Min Sung; Chang, Jin-Hae; Lee, Sang Cheol
Abstract: Blends of poly(lactic acid)s (PLAs) containing three different concentrations of d -isomer (i.e., 1, 4, and 10 mol%; referred to as PLA1, PLA4, and PLA10, respectively) with poly(dl -lactic acid) (PDLLA) were prepared via solution blending. The three PLAs were miscible with PDLLA, as determined by dynamic mechanical analysis. Drawn films of PLA1/PDLLA, PLA4/PDLLA, and PLA10/PDLLA blends exhibited endothermic peaks just above the glass transition temperature, which is evidence of strain-induced enthalpy relaxation. A thermodynamic model for the miscible blend system was applied to determine contributions of intramolecular and intermolecular energy changes to strain-induced enthalpy relaxation for PLA1, PLA4, and PLA10; the resultant values suggested that intramolecular energy changes are mainly responsible for strain-induced enthalpy relaxation. Graphical abstract: Highlights: Drawn films of PLA blends exhibit endothermic peaks just above glass transition temperature. For PLA containing less than 4 mol% of d -isomer, almost 60% of the endothermic heat originates from intramolecular energy change. As the d -isomer content of PLA increases, the contribution of intramolecular energy change to the endothermic heat increases. Overall, intramolecular energy change is primarily responsible for strain-induced enthalpy relaxation.